CAR-T Cells and Oncolytic Viruses: Joining Forces to Overcome the Solid Tumor Challenge - Guedan, Sonia; Alemany, Ramon (Frontiers in Immunology, 2018)
Adoptive transfer of chimeric antigen receptors (CARs)-modified T cells has resulted in unprecedented rates of long-lasting complete responses in patients with leukemia and lymphoma. However, despite the impressive results in patients with hematologic malignancies, CAR-T cells have showed limited effect against solid cancers. New approaches will need to simultaneously overcome the multiple challenges that CAR-T cells encounter in solid tumors, including the immunosuppressive tumor microenvironment and heterogeneity of antigen expression. Oncolytic viruses are lytic and immunogenic anti-cancer agents with the potential to synergize with CAR-T cells for the treatment of solid tumors. In addition, viruses can be further modified to deliver therapeutic transgenes selectively in the tumor microenvironment, which could enhance the effector functions of tumor-specific T cells. This review summarizes the major limitations of CAR-T cells in solid tumors and discusses the potential role for oncolytic viruses as partners for CAR-T cells in the fight against cancer.